2021
DOI: 10.1111/jcmm.16449
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‐mediated pyroptosis of miR‐93‐TXNIP‐NLRP3 leads to functional difference between M1 and M2 macrophages in sepsis‐induced acute kidney injury

Abstract: Sepsis is a systemic inflammatory response syndrome caused by infection, resulting in organ dysfunction. Sepsis‐induced acute kidney injury (AKI) is one of the most common potential complications. Increasing reports have shown that M1 and M2 macrophages both take part in the progress of AKI by influencing the level of inflammatory factors and the cell death, including pyroptosis. However, whether M1 and M2 macrophages regulate AKI by secreting exosome remains unknown. In the present study, we isolated the exos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 46 publications
0
43
0
Order By: Relevance
“…Both M1 and M2 macrophages participate in the process of AKI by influencing the levels of inflammatory factors and cell death, including pyroptosis. Juan et al ( 95 ) proved that M1 and M2 macrophages have opposite effects on the pyroptosis of renal TECs in a co-culture system, which may lead to functional differences of their different phenotypes in the pathology of sepsis-AKI. Additional evidence showed that either CLP or LPS caused macrophage pyroptosis ( 93 , 96 ).…”
Section: Types Of Programmed Cell Death In Sepsis-akimentioning
confidence: 99%
“…Both M1 and M2 macrophages participate in the process of AKI by influencing the levels of inflammatory factors and cell death, including pyroptosis. Juan et al ( 95 ) proved that M1 and M2 macrophages have opposite effects on the pyroptosis of renal TECs in a co-culture system, which may lead to functional differences of their different phenotypes in the pathology of sepsis-AKI. Additional evidence showed that either CLP or LPS caused macrophage pyroptosis ( 93 , 96 ).…”
Section: Types Of Programmed Cell Death In Sepsis-akimentioning
confidence: 99%
“…The regulation of macrophage activation has been under extensive investigation, particularly at the transcriptional and epigenetic levels ( 8 , 27 , 28 ). The latest research has shown that miRNAs are involved in a variety of pathogeneses by regulating macrophage activation ( 29 ). However, although a much larger number of lncRNAs is found in mammalian cells, the role of regulating macrophage activation remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al isolated exosomes from M1 and M2 macrophages, and miRNA sequencing revealed differential miRNA expression levels in M1 and M2 exosomes, in which miR-93-5p was involved in the regulation of mouse renal tubular epithelial cells pyroptosis. It was determined that thioredoxin-interacting protein (TXNIP) was a direct target of miR-93-5p in mouse renal tubular epithelial cells ( 77 ).…”
Section: Immune Cells Promote Various Types Of Programmed Cell Deaths...mentioning
confidence: 99%